Integration Of Life Skills In Futsal Training - Sella Dwi Oktafiani; Oman Hadiana (Universitas Muhammadiyah Kuningan, 2025)
This study developed a futsal training model based on life skills in extracurricular activities at SMP Negeri 1 Kramatmulya using the ADDIE model ( Analysis , Design , Development , Implementation , Evaluation ). The main focus of the development includes emotional control, problem solving, leadership, and respect . The study population consisted of 40 students, all of whom were sampled. Data were collected through observation, interviews, and model validation by subject matter experts and practitioners. The observation results showed that students' life skills were in the sufficient category, with leadership and respect at a better level. The model validation obtained a feasibility score above 80%, indicating that the model was ready for implementation. The integration of life skills in futsal training has been proven to positively contribute to the development of students' character and social-emotional skills. However, aspects of emotional control and problem solving remain major challenges that require further attention. The ADDIE model has proven effective as a framework for developing systematic and needs-based training programs for students.